Nontarget Effects of Preemergence Herbicide Diuron in Hamlin and Valencia Sweet Orange (Citrus sinensis L. Osbek) in Florida - Nirmal Timilsina; Ozgur Batuman; Fernando Alferez; Davie Kadyampakeni; Ruby Tiwari; Ramdas Kanissery (HortScience, 2023)
The prevalence of Huanglongbing (HLB) disease, also known as citrus greening, has compelled the citrus industry to change management practices to increase production. However, these changes, such as enhanced nutrition and irrigation programs, have caused weed proliferation, subsequently leading to increased use of herbicides. Thus, our study evaluated a popular preemergence herbicide active ingredient, diuron, for nontarget impacts on young Hamlin and Valencia sweet orange (Citrus sinensis L. Osbek) trees in two commercial orchards in southwest Florida. The treatments included the preemergence application of diuron at three rates (1.8, 3.6, and 7.3 kg a.i./ha), a weed-checked control (using postemergence herbicides: glufosinate ammonium + saflufenacil), and a nontreated control. The treatments were applied twice (in Fall 2021 and Spring 2022) in a randomized complete block with four replicates. Results indicate that over a 5-month period, the application of diuron generally had no significant impact on citrus root growth. Further, over a 2-month observation period for Hamlin and a 4-month observation period for Valencia, it was found that diuron application had no notable effect on fruit detachment force. Valencia trees treated with diuron high showed higher HLB disease severity at location 1. In addition, Hamlin trees treated with diuron low and medium showed higher fruit drop (∼19% more) than the untreated control at location 1. However, this trend was inconsistent across the locations and cultivars. This result suggests that increased disease severity and fruit drop were not associated with diuron treatment. Thus, our study finds diuron as a tree-safe option for preemergence weed suppression in citrus production, as long as it is used in accordance with the recommended dosage and restrictions stated on the herbicide label.